2015 Asia-Pacific Microwave Conference (APMC) 2015
DOI: 10.1109/apmc.2015.7413491
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable phaser using gain-loss C-sections for radio analog signal processing (R-ASP)

Abstract: Some emerging applications of R-ASP require the radio systems to adapt to dynamic environments. This cannot be achieved using phasers with fixed group delay profiles. Therefore, we introduce here a gain-loss loaded C-section phaser featuring real-time tunability, or reconfigurability, in group delay. This phaser exhibits an all-pass response all the way across its tuning range thanks to a paired and equalized gain-loss C-section unit. A numerical example is provided, where reconfigurability is achieved by tuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Figure 5 shows three different group delay profiles along with the corresponding three different sets of controlling gain. Enhancement of the group delay swing and the reversed slope of the group delay curve is achieved [35,36].…”
Section: Reconfigurable Phaser Using Gain-loss C-sections and Numericmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 shows three different group delay profiles along with the corresponding three different sets of controlling gain. Enhancement of the group delay swing and the reversed slope of the group delay curve is achieved [35,36].…”
Section: Reconfigurable Phaser Using Gain-loss C-sections and Numericmentioning
confidence: 99%
“…This leads to a reconfigurable all-pass phaser, where all-pass amplitude is obtained by cascading a pair of gain and loss loaded C-sections [35,36].…”
Section: Active and Reconfigurable C-section All-pass Phasersmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss is a significant issue in designing the DDSs, especially at group delay peaks [14]. This problem could be solved by inserting an amplifier into a single DDS [14, 15], or between DDSs in the cascading configuration. The second problem is the size of the cascaded structure, which could be solved by inserting DDS into a feedback loop configuration [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that introducing balanced loss and gain in a conventional C-section phaser [24]- [26] equally enhances the overall group delay of the phaser while reversing its magnitude response [27]. Furthermore, using equalized loss-gain pair of C-sections results in a perfect phaser, exhibiting flat (allpass) magnitude and controllable group delay, a response that is impossible in purely passive phasers, where higher group delays are always accompanied with higher loss due to longer time wave trapping, and hence increased dissipation, within the structure.…”
Section: Introductionmentioning
confidence: 99%